2009
DOI: 10.1007/s10493-009-9290-y
|View full text |Cite
|
Sign up to set email alerts
|

Life table and predatory efficiency of Stethorus gilvifrons (Coleoptera: Coccinellidae), an important predator of the red spider mite, Oligonychus coffeae (Acari: Tetranychidae), infesting tea

Abstract: The ladybird beetle, Stethorus gilvifrons, is a major predator of the red spider mite, Oligonychus coffeae, infesting tea. Biology, life table and predatory efficiency of S. gilvifrons were studied under laboratory conditions. Its average developmental period from egg to adult emergence was 19.2 days. After a mean pre-oviposition period of 5.3 days, each female laid an average of 149.3 eggs. Adult females lived for 117.3 days and males for 41.5 days. The life table of the beetle was characterized by an intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 15 publications
2
5
0
1
Order By: Relevance
“…The results of the current study indicated that S. gilvifrons fed on AD1 that lacked E. kuehniella eggs had very close female developmental time (15.50 days), immature survival (70.23%), female longevity (31.18 days), total fecundity (42.09 eggs), egg hatch (72.0%), sex ratio (53.62% female) and r (0.119 d −1 ) values compared to those reported by Ebrahimifar et al [38], suggesting that the nutritional quality of two the artificial diets (AD1 and AD2) was similar. On the other hand, the r values of S. gilvifrons on the artificial diet (AD1) calculated here (0.119 d −1 ) or on a factitious diet (date palm pollen plus E. kuehniella eggs) reported by Ebrahimifar et al [38] The results of our experiments showed that the number of larval instars of S. gilvifrons fed on artificial diets were the same as those reported for this species fed natural prey Oligonychus coffeae (Nietner) [16], T. turkestani and Eutetranychus orientalis Klein [26], T. urticae [44], O. afrasiaticus [21], and T. cinnabarinus [18]. It has been noted that inadequate foods can increase the number of larval instars [45,46], therefore the artificial diets presented to S. gilvifrons in the current study had adequate nutritional quality in comparison to the natural prey (tetranychid mites).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results of the current study indicated that S. gilvifrons fed on AD1 that lacked E. kuehniella eggs had very close female developmental time (15.50 days), immature survival (70.23%), female longevity (31.18 days), total fecundity (42.09 eggs), egg hatch (72.0%), sex ratio (53.62% female) and r (0.119 d −1 ) values compared to those reported by Ebrahimifar et al [38], suggesting that the nutritional quality of two the artificial diets (AD1 and AD2) was similar. On the other hand, the r values of S. gilvifrons on the artificial diet (AD1) calculated here (0.119 d −1 ) or on a factitious diet (date palm pollen plus E. kuehniella eggs) reported by Ebrahimifar et al [38] The results of our experiments showed that the number of larval instars of S. gilvifrons fed on artificial diets were the same as those reported for this species fed natural prey Oligonychus coffeae (Nietner) [16], T. turkestani and Eutetranychus orientalis Klein [26], T. urticae [44], O. afrasiaticus [21], and T. cinnabarinus [18]. It has been noted that inadequate foods can increase the number of larval instars [45,46], therefore the artificial diets presented to S. gilvifrons in the current study had adequate nutritional quality in comparison to the natural prey (tetranychid mites).…”
Section: Discussionsupporting
confidence: 86%
“…The results of our experiments showed that the number of larval instars of S. gilvifrons fed on artificial diets were the same as those reported for this species fed natural prey Oligonychus coffeae (Nietner) [ 16 ], T. turkestani and Eutetranychus orientalis Klein [ 26 ], T. urticae [ 44 ], O. afrasiaticus [ 21 ], and T. cinnabarinus [ 18 ]. It has been noted that inadequate foods can increase the number of larval instars [ 45 , 46 ], therefore the artificial diets presented to S. gilvifrons in the current study had adequate nutritional quality in comparison to the natural prey (tetranychid mites).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…All host plants were irrigated at the same time and no fertilizers or pesticides were used during the experiments. A modified leaf-disc method was used to rear O. litchii in this study (Perumalsamy et al 2010;Rahman et al 2013). A sheet of cotton wool gauze was set in a large Petri dish (46 cm in diam), and distilled water was added to the Petri dish to keep the gauze water-saturated.…”
Section: Leaf Discsmentioning
confidence: 99%
“…The predators belong to Stethorus, Parastethorus and Oligota genera are considered highly effective natural enemies of tetranychid mites (Biddinger et al, 2009;Perumalsamy et al, 2009a;Perumalsamy et al, 2009b). These are incorporated as biological control agents in Integrated Pest Management programs (IPM) since they prey all the stages of tetranychid mites (Hoy, 2011).…”
Section: Introductionmentioning
confidence: 99%